Effects of different concentrations of mannitol on gene expression in Stevia rebaudiana Bertoni - Hashempoor, Somaye; Ghaheri, Matin; Kahrizi, Danial; Kazemi, Nastaran; Muhammadi, Saare; Safavi, Seyed Mehdi; Ghorbani, Tayebeh; Rahmanian, Elham; Heshmatpanaah, Malihe (Cellular and Molecular Biology, 2018)
Stevia rebaudiana Bertoni is one of the most important herbal sweetener plants from Asteracea family that have a lot of Steviol glycosides. Among different methods, tissue culture is the best way with high efficiency that is useful for studying stress tolerance mechanisms to obtain drought tolerance of stevia. For this purpose, different concentrations of mannitol (0, 10, 20, 30, 40, 50 mg/l) were used as various treatments in the culture medium of stevia. According to the results, the highest level of UGT85C2 gene expression (1.181 Total lab unit) was seen in plants grown under 30 mg/l mannitol treatment and the lowest level of this gene expression (0.603 Total lab unit) was observed under 40 mg/l mannitol treatment. However, the highest level of KO gene expression (1.323 Total lab unit) was observed under 20 mg/l mannitol. It shows stevia growth is affected by osmotic stress. Water deficiency has a negative impact on Stevia. However, the expression of genes had increased by particular mannitol concentrations. Actually, stevia can survive under various abiotic stresses.